(untitled) (The Review of Diabetic Studies, 2025)
Prehospital pain management is a critical component of emergency medical services (EMS), directly influencing patient outcomes, satisfaction, and quality of care. Acute pain is highly prevalent among patients requiring paramedic intervention, yet oligoanalgesia, the under-treatment of pain, remains a persistent global challenge. This review examines the epidemiology, assessment, and management of prehospital pain, alongside the historical evolution of paramedic practice, current pharmacological and non-pharmacological strategies, and the unique needs of special populations. It highlights systemic barriers such as inadequate pain assessment, provider concerns regarding drug safety, and regulatory constraints. Advances in pharmacological options, simulation-based education, and emerging innovations including intranasal delivery, portable infusion technology, digital pain assessment, and telemedicine, are expanding paramedic capabilities. Addressing gaps in training, guideline adherence, and equity in pain treatment is essential to ensure timely, safe, and effective analgesia. This synthesis underscores the ethical and clinical imperative of improving prehospital pain management to enhance patient-centered outcomes and strengthen trust in EMS systems.